PL03: Implementation of the Canadian C-Spine Rule by paramedics: a safety evaluation. (15th May 2017) - Vaillancourt, C.; Charette, M.; Sinclair, J.E.; Maloney, J.; Dionne, R.; Kelly, P.; Wells, G.A.; Stiell, I.G.
Abstract : Introduction: The Canadian C-Spine Rule (CCR) was validated by emergency physicians and triage nurses to determine the need for radiography in alert and stable Emergency Department trauma patients. It was modified and validated for use by paramedics in 1, 949 patients. The prehospital CCR calls for evaluation of active neck rotation if patients have none of 3 high-risk criteria and at least 1 of 4 low-risk criteria. This study evaluated the impact and safety of the implementation of the CCR by paramedics.Methods: This single-centre prospective cohort implementation study took place in Ottawa, Canada. Advanced and primary care paramedics received on-line and in-person training on the CCR, allowing them to use the CCR to evaluate eligible patients and selectively transport them without immobilization. We evaluated all consecutive eligible adult patients (GCS 15, stable vital signs) at risk for neck injury. Paramedics were required to complete a standardized study data form for each eligible patient evaluated. Study staff reviewed paramedic documentation and corresponding hospital records and diagnostic imaging reports. We followed all patients without initial radiologic evaluation for 30 days for referral to our spine service, or subsequent visit with radiologic evaluation. Analyses included sensitivity, specificity, kappa coefficient, t-test, and descriptive statistics with 95% CIs.Results: The 4, 034 patients enrolled between Jan. 2011 and Aug. 2015 were: mean age 43 (range 16-99), female 53.3%, motor vehicle collision 51.9%, fall 23.8%, admitted to hospital 7.0%, acute c-spine injury 0.8%, and clinically important c-spine injury (0.3%). The CCR classified patients for 11 important injuries with sensitivity 91% (95% CI 58-100%), and specificity 67% (95% CI 65-68%). Kappa agreement for interpretation of the CCR between paramedics and study investigators was 0.94 (95% CI 0.92-0.95). Paramedics were comfortable or very comfortable using the CCR in 89.8% of cases. Mean scene time was 3 min (15.6%) shorter for those not immobilized (17 min vs. 20 min; p=0.0001). A total of 2, 569 (63.7%) immobilizations were safely avoided using the CCR.Conclusion: Paramedics could safely and accurately apply the CCR to low-risk trauma patients. This had a significant impact on scene times and the number of prehospital immobilizations.